EVALUASI MEKANISME PEMOTONGAN DAN PELAPORAN PAJAK OLEH BENDAHARAWAN PEMERINTAH PADA BADAN PERENCANAAN PENELITIAN DAN PEMBANGUNAN KABUPATEN MINAHASA SELATAN - Tumbel, Arnestha; Karamoy, Herman; Tirayoh, Victorina (GOING CONCERN : JURNAL RISET AKUNTANSI, 2017)
Taxes are the main source of state revenue used to finance development and development. In accordance with the provisions applicable in the taxation field, the party who deducts / taxes the goods derived from the State Revenue and Expenditure Budget (APBN) is the government treasurer. Income tax liability. VAT) and. Tax collection (VAT), among others, is the withholding or collection of income tax article 21, Article 22, Article 23,. The purpose of this study is to find out how the mechanism of cutting and reporting by the National Agency for Research and Development of South Minahasa District. The method used is descriptive analysis. The results of this study indicate Research and Development Planning Agency South Minahasa regency has been carrying out obligations in cutting and article 21, article 22, PPn. However, reporting is delayed from the deadline. We recommend that the Research and Development Planning Agency of South Minahasa Regency always pay attention to the time of reporting to not exceed the time limit specified in order to avoid. Keywords: Deductions & reporting, Income tax, Value added, Government treasurer